Effect of Frequency of Prospekta Administration: Anxiolytic Effect in Wistar Rats - Kirill Svitkin; Elizaveta Morozova; Anna Krasheninnikova; Elena Kardash; Ksenia Ganina; Alexandra Emelyanova; Sergey Tarasov; Oleg Epstein (Dose-Response)
Objectives: The primary objective of this experimental study was to evaluate the severity of the anxiolytic effect of Prospekta, a novel drug for treating cognitive, behavioral, and mental disorders, under different administration regimens. Methods: The pharmacological activity of Prospekta was studied in adult male Wistar rats using the open field test. The drug was administered once, twice, or three times daily over a period of five days. Results: The most pronounced anxiolytic effect was observed with twice-daily administration of Prospekta. This regimen led to an increase in the total distance travelled and enhanced exploratory behaviour, as indicated by a greater number of entries into the center and more time spent in the central zones of the open field arena. Conclusion: Given the nature of Prospekta’s composition, the conventional concept of “dose” is not fully applicable. Therefore, the observed effects may result from the cumulative impact of each administration. Furthermore, as with several other drugs used in neurology and psychiatry, a non-linear relationship between the frequency of administration and the anxiolytic effect was established for Prospekta.